Renal excretion of 1,2-dihydroxynaphthalene (DHN) in firefighting instructors after exposure to polycyclic aromatic hydrocarbons (PAHs) during live fire training - Felix Lang; Daniel Wollschläger; Dipl.-Ing. Stephan Letzel; Bernd Roßbach (Scientific Reports, 2024)
Abstract Exposure of firefighting instructors to polycyclic aromatic hydrocarbons (PAHs) such as naphthalene is unavoidable during live fire training. The study aimed to investigate naphthalene uptake by measuring the urinary excretion of the naphthalene metabolite 1,2-dihydroxynaphthalene (DHN), to describe the DHN elimination kinetics and to evaluate the results by comparison to further biomarkers of PAH exposure. N = 6 male non-smoking firefighting instructors completed five training sessions each in a residential fire simulation unit under respiratory protection. All participants provided two urine samples before and another seven samples within an 18-h-interval after each session. DHN was detected by gas chromatography/tandem mass spectrometry (GC–MS/MS) in all samples (n = 237) with median concentrations ranging from 3.3 µg/g crea. (range 0.9–10.2) before exposure to 134.2 µg/g crea. (43.4–380.4) post exposure. Maximum elimination found 3.3 h (median) after onset of exposure decreased with a mean half-life of 6.6 h to 27.1 µg/g crea. (15.7–139.5) 18 h after training. DHN sensitively indicated a presumed dermal naphthalene intake during training, showing similar elimination kinetics like other naphthalene metabolites. Internal exposure of the participants transiently exceeded exposures determined for non-smokers in the general population, but was lower than at other workplaces with PAH exposure. Despite limited uptake, accumulation is possible with daily exposure.